Toward structural change: Gender transformative approaches - McDougall, Cynthia; Badstue, Lone B.; Mulema, Annet A.; Fischer, Gundula; Najjar, Dina; Pyburn, Rhiannon; Elias, Marlène; Joshi, Deepa; Vos, Andrea (International Food Policy Research Institute, 2021)
Almost a quarter of a century after the Beijing Declaration, and with 10 years left to meet the Sustainable Development Goals, The Guardian announced the SDG Gender Index’s finding that, “Not one single country is set to achieve gender equality by 2030” (Equal Measures 2030 2019, Ford 2019). This aligns with the most recent Global Gender Gap Index, which signals that, on the current trajectory, it will take approximately 170 years to achieve gender equality (WEF 2016)—a wait of seven generations, or two and a half lifetimes for the average woman.